RESTING CORTICAL PET METABOLIC CHANGES IN PSYCHOGENIC NON-EPILEPTIC SEIZURES (PNES). Issue 9 (13th August 2015) - Arthuis, M; Micoulaud-Franchi, JA; Bartolomei, F; McGonigal, A; Guedj, E
Abstract : Objective: Pathophysiology of psychogenic non-epileptic seizures (PNES) is poorly understood. Functional neuroimaging data in various functional neurological disorders increasingly support specific neurobiological dysfunction. However to date no studies have been reported of positron emission tomography in patients presenting PNES. We aimed to examine resting state cerebral metabolism using 2-deoxy-2-[fluorine-18]fluoro-D-glucose positron emission tomography (18FDG-PET) in patients presenting PNES. Method: Sixteen patients being evaluated in a specialist epilepsy centre underwent18FDG-PET because of suspected intractable epileptic seizures. However in all patients the diagnosis was subsequently confirmed to be PNES with no co-existing epilepsy. 18FDG-PET was also performed in 16 healthy controls. A voxel by voxel inter-group analysis was performed to look for significant differences in interictal (resting state) cerebral metabolism. In addition, metabolic connectivity was studied using voxel-wise interregional correlation. Results: In comparison to healthy subjects, group analysis of patients with PNES exhibited significant PET hypometabolism within the right inferior parietal and central region, and within bilateral anterior cingulate cortex. Significant increase in metabolic correlation was found in patients with PNES, in comparison to healthy subjects, between right inferior parietal/central region and bilateral cerebellum, and between bilateral anterior cingulate cortex and left parahippocampal gyrus. Conclusion: This is the first study describing FDG-PET alterations in PNES patients. Although we cannot exclude that our data reflect changes due to co-morbidities, they may indicate dysfunction of neural systems in patients with PNES. Hypometabolism regions might relate to two of the pathophysiological mechanisms that may be involved in PNES, i.e. emotional dysregulation (anterior cingulate hypometabolism) and dysfunctional processes underlying consciousness of self and environment (right parietal hypometabolism).